النقد الأدبي من منظور النقد الثقافي - بوزكري, نوال; قيطون, قويدر (جامعة الوادي - University of Eloued, 2022)
عرف النقد الأدبي منذ أن عرفت الإنسانية الفن والأدب أي منذ زمن لا يمكن تحديده وتطور مع الوقت ليكون أكثر منهجية ودقة، فقد تولدت عنه عدة مناهج ومقاربات تواكب المنجز الأدبي، وتتسابق النظريات النقدية الأدبية في دراسته، ثم جاء النقد الثقافي ليقول كلمته أيضا حول النص الأدبي ويدعو النص إليه ليقاربه. مما أثار جدلا نقديا أن نعرف صورة النقد الأدبي من منظور النقد الثقافي والذي أحدث جلبة بقدومه ومحاورته للنقد الأدبي، سنقف عند النقد الثقافي تعريفا ومنهجا ورؤى. ونعالج قضية الجديد الذي يقدمه للنص الأدبي، وأسباب ثورته على النقد الجمالي رغم ما قدمه هذا الأخير من منجز عظيم. Abstract: Literary criticism has been known since humanity has known art and literature, i.e., since a time that cannot be determined and developed with time to be more systematic and accurate. Several approaches and approaches have been generated from it that keep pace with the literary achievement, and literary criticism theories compete in its study, then cultural criticism came to say its word also about the literary text The text calls for him to approach him. What sparked a critical controversy is that we know the image of literary criticism from the perspective of cultural criticism, which made a fuss by coming and talking to literary criticism. And we address the issue of the new that he presents to the literary text, and the reasons for his revolution against aesthetic criticism, despite the great achievement made by the latter.
Literary Criticism From The Perspective Of Cultural Criticism
مقال
Keywords: النقد الثقافي؛ ; النقد الأدبي؛ ; الأنساق الثقافية؛ ; الجمالية؛ ; المضمر; cultural criticism; Literary criticism; cultural patterns; aesthetic; Implicit